Tantangan Kontemporer Hak Asasi Manusia di Indonesia: Kasus-Kasus Diskriminasi dan Kekerasan yang Menggugah Kesadaran - Salsabila, Mutiara (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Human Rights (HAM) are rights inherent in every person without discrimination. Human rights reflect that the power or rights possessed by individuals have a basic or fundamental nature. Many incidents of human rights violations occur due to a lack of understanding of the basic values inherent in each individual, so that people easily violate the rights of others. However, the protection of human rights in Indonesia still faces various challenges and obstacles from a legal, political, social and cultural perspective. This research discusses several cases of discrimination and violence in Indonesia which show how difficult it is to protect and promote human rights in this country. Some contemporary human rights problems in Indonesia include discrimination and inequality, for example, things that can be done to improve human rights conditions in Indonesia, such as improving the quality of human resources, strengthening law enforcement institutions, developing a culture of human rights, and involving civil society in the implementation of human rights.